2012
DOI: 10.1210/en.2012-1101
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of G Protein-Coupled Receptor Kinase 2 Normalizes Vascular Endothelial Function in Type 2 Diabetic Mice by Improving β-Arrestin 2 Translocation and Ameliorating Akt/eNOS Signal Dysfunction

Abstract: In type 2 diabetes, although Akt/endothelial NO synthase (eNOS) activation is known to be negatively regulated by G protein-coupled receptor kinase 2 (GRK2), it is unclear whether the GRK2 inhibitor would have therapeutic effects. Here we examined the hypotensive effect of the GRK2 inhibitor and its efficacy agonist both vascular (aortic) endothelial dysfunction (focusing especially on the Akt/eNOS pathway) and glucose intolerance in two type 2 diabetic models (ob/ob mice and nicotinamide+streptozotocin-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 45 publications
3
44
1
Order By: Relevance
“…Previously, we reported that the mechanism of clonidine-induced endotheliumdependent relaxation was via the Akt/eNOS signaling pathway and, in diabetes, the impaired clonidine-induced response was determined to be a cause of Akt/eNOS downregulation. [14][15][16]18) Briefly, in this study, we hypothesized that RV and clonidine may have a synergistic effect on Akt/eNOS activation. So, the experiment was designed to investigate the mechanism of vasorelaxation induced by clonidine under RV stimulation in the diabetic and control aortas.…”
Section: Effect Of Rv In Diabetic Micementioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we reported that the mechanism of clonidine-induced endotheliumdependent relaxation was via the Akt/eNOS signaling pathway and, in diabetes, the impaired clonidine-induced response was determined to be a cause of Akt/eNOS downregulation. [14][15][16]18) Briefly, in this study, we hypothesized that RV and clonidine may have a synergistic effect on Akt/eNOS activation. So, the experiment was designed to investigate the mechanism of vasorelaxation induced by clonidine under RV stimulation in the diabetic and control aortas.…”
Section: Effect Of Rv In Diabetic Micementioning
confidence: 99%
“…14,16,18) Measurement of Isometric Force Measurement of the isometric force was performed as described previously. 7,[14][15][16][17][18][20][21][22][23][24][25] Mice were anesthetized with 5% isoflurane and sacrificed by decapitation. The thoracic aortas were removed from mice and put in Krebs-Henseleit Solution (KHS) (consisted of KHS (mmol/L); 118.0 NaCl, 4.7 KCl, 25.0 NaHCO 3 , 1.8 CaCl 2 , 1.2 NaH 2 PO 4 , 1.2 MgSO 4 , and 11.0 glucose) and cut from perivascular fat carefully.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations